To the issue of borderline ovarian tumors - A. G. Solopova; A. Yu. Vlasina; N. A. Makatsariya; V. S. Moskvichyova; L. N. Sandzhieva (IRBIS LLC, 2018)
The article presents updated provisions regarding borderline ovarian tumors in women of reproductive age, including the data on epidemiology, risk factors, clinical aspects, diagnosis, treatment, return of the disease, and women's reproductive potential.